2013
DOI: 10.1002/cncr.27975
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in time from prostate cancer diagnosis to treatment initiation

Abstract: AA patients with prostate cancer experienced longer time from diagnosis to treatment than Caucasian patients with prostate cancer. AA patients appear to experience disparities across all aspects of this disease process, and together these factors in receipt of care plausibly contribute to the observed differences in rates of recurrence and mortality among AA and Caucasian patients with prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 29 publications
4
53
4
Order By: Relevance
“…The reasons for this disparity are complex and not fully understood, but are believed to include differential access to care, including differences in cancer treatment (American Cancer Society, 2013b). Prior studies have demonstrated that compared with CA men, AA men are diagnosed at a later stage (Cohen et al, 2006; Du et al, 2006; Hoffman et al, 2001; Mullins, Onukwugha, Bikov, Seal, & Hassain, 2010) receive less aggressive treatment (Ellis et al, 2013; Godley et al, 2003; Hayn et al, 2011; Holmes et al, 2009; Pisu et al, 2010) and also experience a longer delay from diagnosis to start of treatment (Gross, Smith, Wolf, & Andersen, 2008; Stokes et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…The reasons for this disparity are complex and not fully understood, but are believed to include differential access to care, including differences in cancer treatment (American Cancer Society, 2013b). Prior studies have demonstrated that compared with CA men, AA men are diagnosed at a later stage (Cohen et al, 2006; Du et al, 2006; Hoffman et al, 2001; Mullins, Onukwugha, Bikov, Seal, & Hassain, 2010) receive less aggressive treatment (Ellis et al, 2013; Godley et al, 2003; Hayn et al, 2011; Holmes et al, 2009; Pisu et al, 2010) and also experience a longer delay from diagnosis to start of treatment (Gross, Smith, Wolf, & Andersen, 2008; Stokes et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Investigators have tried to identify and quantify the many factors that contribute to these racial gaps in prostate cancer outcomes [8]. Relative to white men, AA men receive less primary therapy [9][10][11][12][13], later treatment [14], and less adjuvant therapy [15]. Although some treatment disparities between white men and men from other races have narrowed with time, AA men have experienced the opposite trend [16].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, racial disparities may exist because African Americans receive inappropriate treatments more often than White patients. Indeed, Stokes et al, also using data from a SEER-Medicare linked database, showed that the time from diagnosis to treatment was longer for African American men with prostate cancer when compared to White patients in the U.S. [4]. The disparity in treatment delays was greatest for patients with high-risk prostate cancer and the authors suggested that these delays were related to poor access to care, which could contribute to disease outcome disparities.…”
Section: Discussionmentioning
confidence: 99%
“…Such differences in the incidence and mortality of African American men may relate to genetic mutations that promote prostate cancer progression [3]; geographic, socioeconomic, or educational barriers to medical care [4,5]; and/or the efficacy of available treatments, such as radical prostatectomy or radiation therapy, which may not be as effective for African Americans as for White patients. In support of the last potential cause, several studies have shown race to be an independent risk factor for recurrence after definitive prostate cancer treatment [6][7][8][9][10][11].…”
Section: Although These Racial Disparities Have Narrowed In Recent Yementioning
confidence: 99%